PENDIDIKAN KECAKAPAN HIDUP DALAMBINGKAI MORAL SEBAGAI STRATEGI BROAD BASED EDUCATION - Saefur Rochmat (LPMPP Universitas Negeri Yogyakarta, 2005)
Up to now, our educational system have not succeeded in increasing the quality ofmanpower, in which we are in the 132